2018
DOI: 10.3390/environments5010008
|View full text |Cite
|
Sign up to set email alerts
|

Riverine Water Quality Response to Precipitation and Its Change

Abstract: Surface waters are prone to the influences from both natural condition and anthropogenic activities. The aim of this paper was to study the impacts of one natural variable, precipitation, and its change posed by a changing climate on water quality of three rivers in Alberta, Canada. Eleven water quality parameters monitored during the time period of 1988-2014 were used to investigate the impact of precipitation. The results showed the significant dependence of most water quality parameters as well as river flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 38 publications
2
19
1
Order By: Relevance
“…In previous studies, in rivers of east coast of Peninsular Malaysia, Hee et al [7] and Suratman et al [8] found that higher P-and N-based nutrient concentrations in Setiu river occurred in the wet season, probably due to P and N loss from the surrounding areas through soil leaching and land runoff from agricultural land with over-fertilization during the heavy rainfall season. In the current study, by contrast, dilution of nutrient concentrations by higher rainfall in the wet season was probably the main driver for P and N compounds declining from the dry to wet seasons [26]. This result is somewhat similar with Ling et al [27] in Batang Baram, Sarawak province, who reported some of the nutrient concentrations in their study were higher when there was no rain.…”
Section: Effect Of Wet and Dry Seasons On Nutrient Distributionssupporting
confidence: 90%
“…In previous studies, in rivers of east coast of Peninsular Malaysia, Hee et al [7] and Suratman et al [8] found that higher P-and N-based nutrient concentrations in Setiu river occurred in the wet season, probably due to P and N loss from the surrounding areas through soil leaching and land runoff from agricultural land with over-fertilization during the heavy rainfall season. In the current study, by contrast, dilution of nutrient concentrations by higher rainfall in the wet season was probably the main driver for P and N compounds declining from the dry to wet seasons [26]. This result is somewhat similar with Ling et al [27] in Batang Baram, Sarawak province, who reported some of the nutrient concentrations in their study were higher when there was no rain.…”
Section: Effect Of Wet and Dry Seasons On Nutrient Distributionssupporting
confidence: 90%
“…While the assumption that relatively high discharge in the wet season results in an additional dilution and consequently less pollution, such discharge increment will most likely promote the washout from heavily industrialized basins and thus introduces considerable amounts of pollutants to rivers 10 . In other words, the wet season is supposed to reduce the element concentrations in the river's water and then sediment through dilution by increased discharge 129 . However, the additional dilution resulting from increased discharge may be offset by the flushing of uninterrupted deposition of waste in a basin with no proper sanitation infrastructure as the case of the Shatt Al-Arab basin 83 .…”
Section: Discussionmentioning
confidence: 99%
“…; Fan and Shibata ; Rostami et al. ), with particular attention given to temperature effects (e.g., Benitez‐Gilabert et al. ).…”
Section: Next Steps For Climate Change Risk Managementmentioning
confidence: 99%
“…The impact of anthropogenic activities on water quality has been studied extensively (e.g., Jarvie et al 2006;Bowes et al 2014). Several studies have investigated the effect of climate change on riverine water quality (e.g., Tu 2009;Whitehead et al 2009;Fan and Shibata 2015;Rostami et al 2018), with particular attention given to temperature effects (e.g., Benitez-Gilabert et al 2010). However, contaminant transport models have not typically been included in the coupled human-hydrologic modeling systems described above, and water quality concerns have therefore not been directly incorporated into bottomup assessments of broader water system resilience.…”
Section: Surface Water Quality Modelingmentioning
confidence: 99%